Low-Dose Acetylsalicylic Acid Reduces T Cell Immune Activation: Potential Implications for HIV Prevention - Lajoie, Julie; Kowatsch, Monika M.; Mwangi, Lucy W.; Boily-Larouche, Geneviève; Oyugi, Julius; Chen, Yufei; Kimani, Makobu; Ho, Emmanuel A.; Kimani, Joshua; Fowke, Keith R. (Frontiers in Immunology, 2021)
Introduction: Acetylsalicylic acid (ASA) is a well-known and safe anti-inflammatory. At low-dose, it is prescribed to prevent secondary cardiovascular events in those with pre-existing conditions and to prevent preeclampsia. Little is known about how low-dose ASA affects the immune response. In this study, we followed women to assess how ASA use modifies T cells immune phenotypes in the blood and at the genital tract. Methods: HIV uninfected women from Kenya were enrolled in this study and followed for one month to assess baseline responses including systemic/mucosal baseline immune activation. Participants then received 81mg of ASA daily for 6 weeks to assess changes to T cell immune activation (systemic and mucosal) relative to baseline levels. Results: The concentration of ASA measured in the blood was 58% higher than the level measured at the female genital tract. In the blood, the level of ASA was inversely correlated with the following: the proportion of Th17 expressing HLA-DR (p=0.04), the proportion of effector CD4+ T cells expressing CCR5 (p=0.03) and the proportion of CD8+Tc17 expressing CCR5 (p=0.04). At the genital tract, ASA use correlated with a decreased of activated CD4+T cells (CD4+CCR5+CD161+ (p=0.02) and CD4+CCR5+CD95+ (p=0.001)). Conclusion: This study shows that ASA use impacts the immune response in both the systemic and genital tract compartments. This could have major implications for the prevention of infectious diseases such as HIV, in which the virus targets activated T cells to establish an infection. This could inform guidelines on ASA use in women